Topoisomerase I poisons-induced autophagy: Cytoprotective, Cytotoxic or Non-protective - Ahmed M. Elshazly; Polina A. Wright; Jingwen Xu; David A. Gewirtz (Autophagy Reports, 2023)
Topoisomerase I inhibitors represent a widely used class of antineoplastic agents that promote both single-stranded and double-stranded breaks in the DNA of tumor cells, leading to tumor cell death. Topotecan and irinotecan are the clinically relevant derivatives of the parent drug, camptothecin. As is the case with many if not most anticancer agents, irinotecan and topotecan promote autophagy. However, whether the autophagy is cytotoxic, cytoprotective, or non-protective is not clearly defined, and may depend largely upon the genetic background of the tumor cell being investigated. This review explores the available literature regarding the nature of the autophagy induced by these clinically utilized topoisomerase I inhibitors in preclinical tumor models with the goal of determining whether the targeting of autophagy might have potential as a therapeutic strategy to enhance the antitumor response and/or overcome drug resistance.